Resale price maintenance in a successive monopoly model - Markus Dertwinkel-Kalt; Christian Wey (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2023)
We present a model to explain why a manufacturer may impose a minimum resale price (min RPM) in a successive monopoly setting. Our argument relies on the retailer having non-contractible choice variables, which could represent the price of a substitute good and/or the effort the retailer exerts for service provision or advertising. Our explanation for a min RPM is empirically distinguishable from alternative justifications for a min RPM that rely, for instance, on retailer competition and service free riding among retailers. Whether a min RPM benefits or harms consumers depends on-as we show-why a min RPM is implemented: if the goal is to soften competition with the substitute product, it tends to harm consumers, and if the goal is to secure service provision, it tends to benefit consumers.
Keywords: L12; L41; D42; K21; 330; Resale Price Maintenance; Vertical Restraints; Cost Pass-Through; Retailing